TEACHERS’ PERCEPTIONS ON THE USE OF PEER- CORRECTION AND SELF-CORRECTION TECHNIQUE TO TEACH WRITING - Mustika; Ampa, Hj. Andi Tenri; Andi Baso , Farisha (FKIP Unismuh Makassar, 2023)
This study aims to determine the teacher's perception of the use of peer-correction and self-correction techniques to teach writing. This research method is a qualitative descriptive method. Research data were collected through interviews. Data were taken from two English teachers at SMAN 5 SELAYAR.The results of the study reveal that teachers believe that Peer-Correction and Self-Correction Techniques in Teaching Writing have a positive influence on students to gain knowledge, especially in writing lessons. In addition, Peer-Correction and Self-Correction techniques are suitable for use at every level of students. The researcher also found that the teacher had an important role in determining the type of material that was suitable for the learning objectives.